Cassiano Branco. Modern visions of an “inconvenient” architect - Pinto, P. T. (2017)
Cassiano Branco (1897-1970) belonged to the pioneer generation of modern Portuguese architects, which worked during the years of the dictatorship regime. During the 30s, Cassiano produced an anti-conservative and eloquent architecture, contrasting with the guidelines of the regime. The discomfort about his personality came also from his ideological opposition to the government. Among his counterparts he has been considered ‘an exception to the rule’, working, mainly for private investors, on programs for renting house buildings, movie theaters and tourism facilities, which were built over the boulevards outlined in Lisbon or in the natural and intact regional scenarios of Portugal.